The Validity and Reliability of the Intercultural Learning Materials Model (ILM) for Drama Subject - Eripuddin, Eripuddin; Rahayu, Pipit; Jufrizal; Agustina (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2023)
The lecturers still seem unconfidence to teach English as Foreign Language. They need the learning material to reveal the gap between English and the student’s own culture. This study aims to find out the validity and reliability of the intercultural learning material for Drama subject. The research design was quantitative research. The instrumentation of this research was the questionnaire. The subject of this research was 29 students. The results showed that the validity of the ILM model was 92,5 %. It means that the ILM model is valid to use for Drama subject. Then, reliability of intercultural learning materials was 0.774; the ILM model is reliable to use for Drama subject. Based on this result, the intercultural learning materials can implemented because they were categorized as valid and reliable. Thus, the learning materials will be an alternative to link between English and Malay cultures in the lesson process and drama performances.